1990
DOI: 10.1051/lait:199028
|View full text |Cite
|
Sign up to set email alerts
|

New results in the volatile odorous compounds of French cheeses

Abstract: The volatile odorous constituents of five French blue cheeses (three Roquefort, a Bleu des Causses and a Bleu d'Auvergne) were isolated by high vacuum distillation, separated by gas chromatographie analysis and subjected to mass spectral analysis. One hundred and twenty nine compounds were identified and quantified. Methyl ketones were the majors compounds for ail cheeses and represented 50 to 75% of the total odorous profile. Secondary alcohols, esters were abundant, especially in the Roquefort sampi es. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
86
0
6

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(100 citation statements)
references
References 22 publications
8
86
0
6
Order By: Relevance
“…High quantities of these compounds are usually present in mold-ripened cheeses and also in most hard cheese such as Parmigiano and Cheddar (Barbieri et al, 1994;Bellesia et al, 2003;Engels et al, 1997;Liebich, Douglas, Bayer, & Zlatkis, 1970). Primary and secondary alcohols, which contribute with fruity and nutty notes to the flavor of cheese (Gallois & Langlois, 1990), have been identified; 1-pentanol, 1-hexanol and 1-heptanol were more abundant than other alcohols. 3-Methyl-l-butanol has been also identified; it is produced by the reduction of the corresponding aldehyde which is derived from the amino acid leucine (Larrayoz, Addis, Gauch, & Bosset, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…High quantities of these compounds are usually present in mold-ripened cheeses and also in most hard cheese such as Parmigiano and Cheddar (Barbieri et al, 1994;Bellesia et al, 2003;Engels et al, 1997;Liebich, Douglas, Bayer, & Zlatkis, 1970). Primary and secondary alcohols, which contribute with fruity and nutty notes to the flavor of cheese (Gallois & Langlois, 1990), have been identified; 1-pentanol, 1-hexanol and 1-heptanol were more abundant than other alcohols. 3-Methyl-l-butanol has been also identified; it is produced by the reduction of the corresponding aldehyde which is derived from the amino acid leucine (Larrayoz, Addis, Gauch, & Bosset, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…The curds were transferred to 1 kg round polyvinylchloride containers, kept at room temperature (20± 2°C) for 2 h, and then placed in a cooling chamber (12± 0.5°C, 80-90 % RH), for 24 h. Cheeses were stored at 4°C. After 24 h of preparation, the cheeses were analyzed for protein, fat and moisture by Kjeldahl method, Gerber method and oven drying, respectively (AOAC 1995) and for lipolysis degree (Gallois and Langlois 1990). Composition results were reported in dry basis.…”
Section: Whole Milk Compositionmentioning
confidence: 99%
“…Hexanoic acid ethyl ester and dodecanoic acid ethyl ester displayed the highest intensities. Several authors [2,13] have suggested that most esters have floral and fruity notes and may contribute to aroma by minimising the sharpness and bitterness imparted by fatty acids and amines, respectively. Few published studies address the odour threshold of esters in cheese, although the range of concentrations and sniffer scores recorded here highlight the sensory impact of these compounds.…”
Section: Characterisation Of Volatile Compoundsmentioning
confidence: 99%